2013
DOI: 10.5507/bp.2012.004
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tissue oxygenation during standard CPB and miniaturized CPB (direct oxymetric tissue perfusion monitoring study)

Abstract: Aim. The aim of this study was to compare the impact of standard cardiopulmonary bypass (CPB) with mini CPB on peripheral tissue perfusion. Methods. 24 patients with ischemic heart disease scheduled for CPB were randomised to two groups: Group A (12 patients, standard CPB) and Group B (12 patients, mini CPB). Oxygen tension was measured with an optical multiparametric sensor inserted into the patient's deltoid muscle. Results. Lower priming in Group B (870 ± 221 mL) vs. Group A (1502 ± 48 mL) and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This has been extensively studied by Bennett et al and Mandak et al, who both confirmed that relatively low flow with MiECC is associated with preserved oxygen delivery and is well tolerated by the body, explained by markedly reduced hemodilution. 34,35 Moreover, it has been proved that MiECC optimizes microvascular perfusion by pre-serving and enhancing recovery of microcirculatory blood flow. 36,37 Loss of this balance due to conversion from a closed to an open circuit, as shown in our study, leads to hemodultion and increased lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…This has been extensively studied by Bennett et al and Mandak et al, who both confirmed that relatively low flow with MiECC is associated with preserved oxygen delivery and is well tolerated by the body, explained by markedly reduced hemodilution. 34,35 Moreover, it has been proved that MiECC optimizes microvascular perfusion by pre-serving and enhancing recovery of microcirculatory blood flow. 36,37 Loss of this balance due to conversion from a closed to an open circuit, as shown in our study, leads to hemodultion and increased lactate production.…”
Section: Discussionmentioning
confidence: 99%